Authentication of electronic evidence in cybercrime cases based on Malaysian laws and Islamic laws - Mustapha Sa'di, Mursilalaili; Mohamed, Duryana; Kamarudin, Abdul Rani; Ramlee, Zulfakar (2014)
Electronic evidence is one of the many forms of documentary evidence. It is stored and retrievable from electronic devices such as computer and smartphone, particularly in their hard disks or memory banks. However, the fragile nature of electronic evidence, make its prone to damage or susceptible to alteration as well as destruction, due to improper handling of self keeping. Since it can easily be tampered or self-deteriorate, establishing its authenticity and reliability of electronic evidence is a technical task. These states of affair would cause such electronic evidence to be inadmissible or carries low weightage by the court thus undermining the prosecution’s or the plaintiff’s case, as the case may be. In order to ensure such evidence is admissible and carry the expected weightage, the parties must first prove the authenticity of such evidence, and subsequently on its reliability and relevancy. Nevertheless, in cybercrime cases, proving the crime is actually a technical challenge, where the responsible personnel are required to understand what is electronic evidence, how to extract and preserve the originality of such evidence and the laws governing electronic evidence as well as cybercrimes. This article attempt to explain scope of electronic evidence in regulation to criminal cases as far as its admissibility and weightage are concern. The discussion will be based on Malaysian laws, Islamic laws and common law.